High-Quality Epitaxial Cobalt-Doped GaN Nanowires on Carbon Paper for Stable Lithium-Ion Storage - Peng Wu; Xiaoguang Wang; Danchen Wang; Yifan Wang; Qiuju Zheng; Tailin Wang; Changlong Sun; Dan Liu; Fuzhou Chen; Sake Wang (Molecules)
Due to its distinctive structure and unique physicochemical properties, gallium nitride (GaN) has been considered a prospective candidate for lithium storage materials. However, its inferior conductivity and unsatisfactory cycle performance hinder the further application of GaN as a next-generation anode material for lithium-ion batteries (LIBs). To address this, cobalt (Co)-doped GaN (Co-GaN) nanowires have been designed and synthesized by utilizing the chemical vapor deposition (CVD) strategy. The structural characterizations indicate that the doped Co elements in the GaN nanowires exist as Co2+ rather than metallic Co. The Co2+ prominently promotes electrical conductivity and ion transfer efficiency in GaN. The cycling capacity of Co-GaN reached up to 495.1 mA h g−1 after 100 cycles. After 500 cycles at 10 A g−1, excellent cycling capacity remained at 276.6 mA h g−1. The intimate contact between Co-GaN nanowires and carbon paper enhances the conductivity of the composite. Density functional theory (DFT) calculations further illustrated that Co substitution changed the electron configuration in the GaN, which led to enhancement of the electron transfer efficiency and a reduction in the ion diffusion barrier on the Co-GaN electrode. This doping design boosts the lithium-ion storage performance of GaN as an advanced material in lithium-ion battery anodes and in other electrochemical applications.